The ERC Project Before Copyright: An Interim Report from the Field - Campillo Pardo, Alberto José; Buning, Marius; Ottone, Andrea; Citron, Nana (Studi Politici, 2025)
The article introduces the research project ‘Before Copyright: Printing Privileges and the Politics of Knowledge in Early Modern Europe’ (ERC, 101042034) to the academic community, through a detailed explanation of its historical context, methodological approach, and main hypotheses. It also outlines the preliminary findings of the project and describes the individual sub-projects that are being developed by the project members. In doing so, the essay explores the project’s potential contribution to the study of early modern European history.